Postpartum LARC Among the Privately Insured—Use After Preterm and Term Births [23J]. (May 2020) - Goldthwaite, Lisa; Maric, Ivana; Shaw, Kate A.; Stevenson, David K.; Shaw, Gary
Abstract : INTRODUCTION: Sub-optimal interpregnancy interval (IPI) and prior preterm delivery are risk factors for preterm birth. Provision of long acting reversible contraception (LARC) in the postpartum period may optimize IPI and thereby decrease the risk of a subsequent preterm birth. However, postpartum LARC uptake has not been investigated among those with a prior preterm delivery who are privately insured. METHODS: We used the national IBM MarketScan® Commercial Database to identify singleton deliveries from 2007-2016, spontaneous preterm birth, and follow up within 12 weeks postpartum. We compared LARC placement after preterm and term deliveries across years and by state. RESULTS: Among 3, 132, 107 singleton deliveries, 6.6% were preterm. Over the time period, postpartum LARC use more than doubled: 4.8% to 11.5% for intrauterine devices (IUDs), 0.1% to 2.3% for implants. In 2016, compared to term cohort, the preterm cohort was less likely to receive IUDs (10.1% vs 11.7%, P< .0001), as likely to receive implants (2.5% vs 2.3%, P= .15) and more likely to present for postpartum care (62% vs 56%, P< .0001). Placement of LARC prior to hospital discharge was exceedingly rare in both cohorts (preterm: 8 per 10, 000 deliveries vs term: 7 per 10, 000 deliveries, P= .05). State level analysis showed postpartum LARC use widely varied, by state (range 6%-32%). CONCLUSION: While postpartum LARC is increasing among the privately insured, exceedingly few receive LARC prior to hospital discharge. Postpartum follow-up is alarmingly low, highlighting the importance of inpatient LARC access. Variable state-level uptake and private reimbursement warrant ongoing surveillance and efforts to remove barriers to postpartum LARC for all.